(untitled) (Academic Journal of Internal Affairs, 2023)
Aim: We present an extremely rare case in this article. A transgender adolescent was admitted to the Department of Child and Adolescent Psychiatry at the Heim Pál National Institute of Pediatrics in September 2021 due to delusional pregnancy and peer relationship conflicts. The 17-year-old child was convinced she was pregnant with twins, although she was born as a boy. The psychopathological and criminological aspects of the case are outlined. Methodology: The psycho-diagnostic background was based on traditional Hungarian diagnostic protocol. It consisted of projective tests. Criminological characteristics were explored by analysing the most recent international literature. In both aspects we used our own clinical and victim protection experience. Findings: We concluded that the psychological and criminological development pathways of the adolescent in the case study intersected at several points, and that these issues escalated along the child’s victimization. Value: We highlighted that child sexual exploitation is a systematic problem. Not only the cohesion of society is threatened, but the effectiveness of social care institutions and law enforcement can be also damaged. At the end of our article, we outlined a hypothesis that the indirect causes of transgender violence can be found in sexual exploitation and the immanent harms of institutionalisation.